Strategi Komunikasi Generasi Baru Indonesia Solo pada Sosialisasi QRIS Sebagai Literasi Penggunaan Pembayaran Non Tunai di Kota Solo - widias ningrum, evilia hera; Kusumo Aji, Haryo; Widiyowati, Estu (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2024)
QRIS (Quick Response Code Indonesian Standard) is one of the technological developments in the field of non-cash payment systems whose aim to make transactions easier. The low level of knowledge of the people of Solo City about QRIS has resulted in the lack of interest of the people of Solo City in using QRIS. GenBI Solo is a community of Bank Indonesia scholarship recipients whose aim to communicate Bank Indonesia policies. Researchers used Anwar Arifin's communication strategy with a qualitative approach. Data obtained through interviews, observation and literature study. The aim of this research was to find out the communication strategy used by GenBI Solo in socializing the QRIS program as a literacy tool for the Solo city community in the use of non-cash payments. The results of this research were: (1) getting to know the audience for QRIS socialization, namely UMKM and buyers. (2) formulate the objective, namely to introduce and explain the advantages of QRIS and receive complaints from the people of Solo City regarding QRIS, (3) compose a message that is easy to understand, packaged attractively and follows operational standards using the resolving and persuading method. (4) media selection as an information medium.